Role of Public Speaking and The Development of Personal Characteristic on The Performance of Amil Baznas of Kalimantan Selatan Province: Peran Public Speaking dan Pengembangan Karakteristik Personal Pada Kinerja Amil Baznas Provinsi Kalimantan Selatan - Akhmad Anwari; Arafah Arafah; Ria Puspita Sari; Shanty Komalasari; Musfichin (Yayasan Ahmar Cendekia Indonesia, 2022)
There are several factors that support the success of a company's goals and objectives, namely a business in skills that has been carried out by the amil of Baznas of South Kalimantan Province. To improve amil performance, it is necessary to develop public speaking and personal characteristics. The purpose of this study was to find out whether public speaking and the development of personal characteristics have an influence on the performance of amil, and what impact will occur in the company if there is an influence of public speaking and the development of these characteristics. Public speaking is an ability to speak to many people and individually in conveying a purpose that can be understood by the listener. Personal characteristics are ways of interpreting and seeing certain things including age, sex, marital status in the organization. The research method used in this research is to use the literature study method through a qualitative approach. Which type of qualitative literature study or literature study is a research stage carried out through library sources, either primary or secondary. The result of this research is that the public speaking Workshop has succeeded in improving the quality of public speaking and understanding of the characteristics seen from the results of the questionnaires that have been filled out by the Amil BAZNAS of south Kalimantan Province that after the workshop they know some tips to minimize nervousness and increase confidence when communicating and easy to understand. Interlocutor because they know the tips that have been given. Abstrak Terdapat beberapa faktor yang menunjang keberhasilan sebuah cita-cita dan tujuan dari suatu perusahaan yakni sebuah usaha dalam keterampilan yang telah dilakukan oleh amil Baznas Provinsi Kalimantan Selatan. Untuk meningkatkan kinerja amil maka perlu yang namanya pengembangan public speaking dan karakteristik personal. Tujuan penelitian ini diadakan agar dapat mengetahui apakah public speaking dan pengembangan karakteristik personal memilik pengaruh terhadap kinerja amil, dan apa dampak yang akan terjadi di perusahaan jika terdapat pengaruh public speaking dan pengembangan karakteristik tersebut. Public speaking adalah sebuah kemampuan berbicara terhadap orang banyak maupun perindividu dalam menyampaikan suatu maksud dan tujuan yang dapat dimengerti oleh sipendengar (Fitria, 2022). Karakteristik personal adalah cara menafsirkan dan melihat suatu hal tertentu mencakup usia jenis kelamin status perkawinan dalam organisasi. Metode penelitian yang dilakukan dalam penelitian ini yaitu menggunakan metode studi pustaka melalui jenis pendekatan kualitatif. Yang mana jenis kualitatif studi pustaka atau studi literature ini merupakan tahapan penelitian yang dilaksanakan melalui sumber kepustakaan, baik berupa primer ataupun skunder (Ekayanti et al., 2019). Hasil Penelitian ini adalah Workshop Public Speaking berhasil meningkatkan kualitas Public Speaking dan pemahaman tentang karakteristik terlihat dari hasil kuesioner yang telah diisi amil Baznas Provinsi Kalimantan Selatan bahwa mereka setelah adanya workshop tersebut mengetahui beberapa tips untuk meminimalisir rasa gugup dan meningkatkan percaya diri ketika berkomunikasi dan mudah memahami lawan bicara karena mengetahui tips yang telah diberikan.